Control of pore geometry on the strength, elastic anisotropy and acoustic emission output of vesicular lavas from Nevados de Chillán, Chile - Fernanda Merchán; John Browning; Gloria Arancibia; David Healy; Valentina Mura; Camila Pineda; Michael J. Heap; Patrick Baud; Jorge E. Romero; Matias Clunes; Luis Felipe Orellana; Diego Morata (Bulletin of Volcanology, 2026)
The strength and stiffness of lavas, as well as their propensity to fracture and develop permeable flow networks, are all governed by microstructural heterogeneity. In vesicular andesitic–dacitic lavas from the Nevados de Chillán Volcanic Complex (NChVC) in Chile, we show that uniaxial compressive strength (UCS) and Young’s modulus (E) depend not only on connected porosity but also on the distribution, orientation, size and aspect ratio of pores. Pore fabrics were first quantified via 2D analyses (transparent sections and surface imaging) and 3D micro–computed tomography (micro-CT). Then, using cylinders with pores aligned parallel, perpendicular, and inclined to the loading direction, we performed UCS tests instrumented with acoustic emission (AE) monitoring. Loading perpendicular to the pore major axis presents the lowest strength and stiffness and triggers AE output at low stress, whereas loading parallel to the pore major axis initiates damage at higher stress, attains relatively higher strength, and culminates in macroscopic failure with higher rates of AE concentrated near the peak stress. Mixed AE patterns are observed when loading at an inclined angle to the pore major axis. These observations are consistent with the theory of microcrack nucleation and propagation controlled by stress concentration around elliptical pores. While porosity exerts a first-order control on the overall magnitude of strength and stiffness, we conclude that pore alignment, aspect ratio and directional variability fundamentally modulate failure style, damage evolution, and rock mechanical properties. Operationally, this framework anticipates preferential directions of weakness and damage evolution prior to failure, thereby supporting assessments of the mechanical stability of lava domes, levees, and scoria cones composed of high porosity materials.

Analysing ecosystem and demersal stocks dynamics in the Chilean Patagonia system (41°28.6′S–57°S) from 1980 to 2020 using food web modelling - Sergio Neira; Hugo Arancibia; Mónica E. Barros; Ana Arriagada; Rubén Alarcón; Claudio Gatica (Progress in Oceanography, 2026)

Temporal evolution of fumarolic gas geochemistry at the Nevados de Chillán Volcanic complex (2013−2023): Signals of volcanic unrest and insights into the hydrothermal system - Daniele Tardani; Marco Taussi; Franco Tassi; Jorge E. Romero; Philippe Robidoux; Camila Poblete-González; Fernanda Álvarez-Amado; Lorenzo Manosalva; Claudia Berrios; Daniele L. Pinti; Martin Reich; Diego Morata; et al. (Journal of Volcanology and Geothermal Research, 2025)

Wind Is a Primary Driver of Fungal Dispersal Across a Mainland‐Island System - D. Naranjo‐Orrico; O. Ovaskainen; B. Furneaux; J. Purhonen; P. A. Arancibia; S. Burg; N. Moser; J. Niku; G. Tikhonov; E. Zakharov; N. Monkhouse; N. Abrego (Molecular Ecology, 2025)
Dispersal is one of the main processes shaping ecological communities. Yet, for species‐rich communities in natural systems, the role of dispersal in community assembly remains relatively less studied compared to other processes. This is the case for fungal communities, for which predictable knowledge about where and how the dispersal propagules move across space is largely lacking. We sampled fungal communities at their dispersal stage in a lake mainland‐island system in Finland, using a regular grid of 18 × 18 km, including sites on the mainland, islands and over the water. Fungal communities were screened by applying DNA barcoding to air samples. To assess the factors determining fungal dispersal, we modelled aerial fungal communities with a joint species distribution model, including spore traits, weather‐related predictors, and spatial predictors. We found that the probability of occurrence of most species (and consequently species richness measured as the number of OTUs per sample) was lower in low‐connectivity sites (water and isolated islands) compared to high‐connectivity sites (mainland). There was a strong phylogenetic signal in how the fungal species responded to connectivity, indicating that some taxonomic groups are more dispersal limited than others, although such responses were not structured by their trophic guilds. Furthermore, wind speed influenced how species with different spore sizes responded to connectivity: in low‐connectivity sites, species with large sexual spores were detected especially when wind was high, whereas, in high‐connectivity sites, they were detected especially when wind was low. This study demonstrates that air fungal dispersal might be more predictable than previously considered and contributes to the mechanistic understanding of fungal air dispersal.

Using a time-dynamic food web model to compare predation and fishing mortality in Pleuroncodes monodon (Galatheidae: Crustaceae) and other benthic and demersal resource species off central Chile - Mónica E. Barros; Ana Arriagada; Hugo Arancibia; Sergio Neira (Ecological Modelling, 2024)

How sensitive are catchment runoff estimates to on-farm storages under current and future climates? - David E. Robertson; Hongxing Zheng; Jorge L. Peña-Arancibia; Francis H.S. Chiew; Santosh Aryal; Martino Malerba; Nicholas Wright (Journal of Hydrology, 2023)

Characterising the regional growth of on-farm storages and their implications for water resources under a changing climate - Jorge L. Peña-Arancibia; Martino E. Malerba; Nicholas Wright; David E. Robertson (Journal of Hydrology, 2023)

Stomach contents and stable isotope analysis reveal ontogenetic shifts and spatial variability in Brama australis diet - Sebastian A. Klarian; Eric T. Schultz; María Francisca Hernández; Juan Antonio Valdes; Francisco Fernandoy; Mónica E. Barros; Sergio Neira; Hugo Arancibia (Environmental Biology of Fishes, 2022)

Occurrence, distribution and dynamics of perchlorate in soil, water, fertilizers, vegetables and fruits and associated human exposure in Chile - R. Calderón; P. Palma; N. Arancibia-Miranda; Un-Jung Kim; E. Silva-Moreno; K. Kannan (Environmental Geochemistry and Health, 2022)

Effect of Pinus ponderosa afforestation on soilborne Frankia and saprophytic Actinobacteria in Northwest Patagonia, Argentina - Natalia B. Arancibia; Mariana Solans; M. Cecilia Mestre; Eugenia E. Chaia (Symbiosis, 2018)

Tectono-metallogenetic evolution of the Fe–Cu deposit of Dominga, northern Chile - E. Veloso; J. Cembrano; G. Arancibia; G. Heuser; S. Neira; A. Siña; I. Garrido; P. Vermeesch; D. Selby (Mineralium Deposita, 2017)

Productivity of a Continuous Mining System for Block Caving Mines - L. F. Orellana; R. Castro; A. Hekmat; E. Arancibia (Rock Mechanics and Rock Engineering, 2017)